Influência da adição de resíduo siderúrgico na performance do concreto - Janaina Alves Almeida (2009)
The reinsertion of waste production processes seeking to attend theenvironmental issue is being widely discussed in national and international forum. In the face of the observation that industries of manufacture and processing produce waste which are not always properly used, must-propose studies aiming at alliance the use of waste to issues related to sustainability This work evaluates the influence of adding steel residue in the performance of concrete. The concrete were produced with the replacement of part of cement by blast furnace slag, material obtained in significant quantities in steel, in the process of reduction of iron ore. The influence of adding was evaluated by comparing a concrete reference with concrete replacing part of cement by blast furnace slag in percentages of 12.5%, 20% and 35%. The assessment of the durability of concrete, both of reference for the concrete replacing part of cement by blast furnace slag, subjected to chemical attack was performed through absorption tests and losses in mass, before and after attack by sulfuric acid, a concentration of 2,5%.The concrete with the various substitutes were compared with the concreteness of reference of the results of tests, demonstrating that the concrete with replacement of 12.5% is the most indicated by presenting a compression resistance of 26MPa, an absorption of 5% and not to have a significant loss of mass compared with the concreteness of reference.May-conclude that the interface between the different knowledge areasrepresents a fundamental condition to take account of the economic, cultural and social aiming an equal society and sustainable development.